Respuestas

2012-06-17T21:09:05+02:00

Demostraciones

 

1)       sen^{2}x +cos^{2} x = (sen x)(cscx)

 

sen^{2}x +cos^{2} x = (sen x)( \frac{1}{senx})

 

sen^{2}x +cos^{2} x = 1

 

 

2) tan^{2}x + (senx)(cscx)= sec^{2} x

 

tan^{2}x + (senx)(\frac{1}{senx})= sec^{2} x

 

tan^{2}x + 1= sec^{2} x

 

 

3)  \frac{1}{csc^{2}} +cos^{2}x = 1

 

sen^{2}x +cos^{2} x = 1

 

 

4) \frac{1}{tan^{2}x}+ 1 = csc^{2}x

 

cot^{2}x + 1 = csc^{2}x

 

5) \frac{sen^{2}x}{cos^{2}x} + 1 = sec^{2}x

 

tan^{2}x+ 1 = sec^{2}x

 

 

Puedes encontrar ejercicios parexidos en la sig pag 

 

http://www.fic.umich.mx/~lcastro/identidades%20trigonometricas.pdf